Влияние толщины проволоки из никелида титана на ее механические характеристики - Ковалева, Марина Андреевна (Перспективы развития фундаментальных наук. Т. 1 : сборник научных трудов XIX Международной конференции студентов, аспирантов и молодых ученых, 26-29 апреля 2022 г.)
The study considers the deformation behavior of thin TiNi wires 40-90 jum in diameter under uniaxial tension. With an increase in thickness, the value of the ultimate strength, the critical stress of martensitic shear, and the amount of reversible strain increase with an increase in the diameter of the tested wire. The study of fracture surfaces shows the presence of two zones with a flattened granular relief and a pitted relief.